Socio-demographic Determinants of Appropriate Utilization of Oral Rehydration Solution Therapy in Under Five Children with Acute Watery Diarrhoea: A Hospital Based Study - Hasan, Md Rabiul; Chowdhury, Tahmina Jahan; Akther, Naznin; Rahman, Zainab; Ullah, Gazi Sabir (Journal of Rangpur Medical College, 2026)
Background: Acute watery diarrhea (AWD) continues to be a primary cause of morbidity and mortality in children under five. Oral rehydration solution (ORS) is a simple and affordable technique demonstrated to minimize the complications and death associated with dehydration. Objective: The effective use of ORS is frequently affected by parental socio-demographic factors. Methods: The cross-sectional study was carried out at the Department of Paediatrics, Jalalabad Ragib - Rabeya Medical College Hospital (JRRMCH), Sylhet. All children under the age of 5 years with AWD admitted to the paediatrics ward comprised the study population. Among them, a total of 300 children were selected with purposive sampling. The duration of the study was 6 months. A questionnaire was used to collect data on the sociodemographic characteristics of the study population, as well as maternal knowledge and practices regarding oral rehydration solution (ORS) and their impact on appropriate utilization of ORS were documented. Results: Most of the mothers (67%) correctly prepared ORS but only 54.3% utilized it appropriately. Among the 300 children, most of them belonged to 1 to 2 years of age group and male children were affected by diarrhoea more (61.7%), but inappropriate utilization of ORS was also predominant in male children (p <0.05). Most of the mothers were in 20 to 30 years of age (75%), resided in rural areas (77%) and were home makers (95.3%). Parents with higher education and better financial condition were associated with improved utilization of ORS (p<0.05). Fathers having business or in service were found utilizing ORS more efficiently than farmers (p <0.05). Apart from sociodemographic factors, maternal knowledge regarding ORS also influenced appropriate use of it. More than 97% of mothers knew about ORS while only 10.7% accurately knew its purpose of replacing salt and water and this group had used ORS significantly better than other groups. Approximately half of the mothers were advised by doctors and good number of them used ORS appropriately (p<0.05). Only 48 % of mothers knew the preservation time of ORS. Majority of the mothers (38%) used cup- spoon for providing ORS to their children, and 75.3% mothers also took ORS along with their children. Food restriction was also a common practice during diarrhoealillness including both babies (59.7%) and mothers (45.7%). Conclusion: This study showed that most of the mothers were familiar with ORS and its preparation. There were several factors which influenced the appropriate utilization of ORS including gender, parental education, monthly income, source of information and knowledge regarding function of ORS. J Rang Med Col.2026 Mar;11(1): 111-118